No morality, no self Anscombe's radical skepticism - Doyle, James, 1963 November 18- (Harvard University Press, 2018)
It is becoming increasingly apparent that Elizabeth Anscombe (1919-2001), long known as a student, friend and translator of Wittgenstein, was herself one of the most important philosophers of the twentieth century. No Morality, No Self examines her two best-known papers, in which she advanced her most amazing theses. In 'Modern Moral Philosophy' (1958), she claimed that the term moral, understood as picking out a special, sui generis category, is literally senseless and should therefore be abandoned. In 'The First Person' (1975), she maintained that the word 'I' is not a referring expression: in other words, its function in the language is not to pick out the speaker, or 'the self' - or any entity whatsoever. Both papers are considered influential, and are frequently cited; but their main claims, and many of their arguments, have been widely misunderstood. In this book James Doyle shows that once various errors of interpretation have been cleared away, the claims can be seen to be far more plausible, and the arguments far more compelling, than even her defenders have realized. Philosophers often seek attention by making startling claims which are subsequently revealed as little more than commonplaces wrapped in hyperbole. Doyle's book makes it clear that here, in her greatest papers, Anscombe achieves something vanishingly rare in philosophy: a persuasive case for genuinely unsettling and profound conclusions. The two lines of argument, seemingly so disparate, are also shown to be connected by Anscombe's deep opposition to the Cartesian picture of the mind.--